Archaeomagnetic dating of the fortification of the Veľká Morava Period in Majcichov - ORLICKÝ, Oto; FOTTOVÁ, Eva; RUTKAY, Matej; TIRPÁK, Ján (Contributions to Geophysics and Geodesy, 2021)
Eight archaeological samples collected from the baked fortification near Majcichov Village were studied by the Thellier's method. The following characteristics were derived from the results of the laboratory measurements: the intensity of the ancient magnetic field F = 0.71677 milli Tesla; the coordinates of the virtual geomagnetic pole VGP: φp = 79.5°, λp = 3.7°; the virtual dipole moment VDM = 10.4 × 10–25 Gauss·cm–3. The relations of derived data with those summarized by Bucha (1975) for the Central Europe have allowed to suggest that the archeological object near Majcichov was baked in the end of 9th Century A.D. This archaeomagnetic dating has been supported also by the archeological findings of the same age.